Arsenic biotransference to alfalfa (Medicago sativa) - Pérez Carrera, Alejo Leopoldo (2014)
The arsenic (As) concentration in the edible part of crops depends on the availability of the As present in the soil and the ability of a crop to take up As and translocate it to the target organs. The aim of this study was the determination of As concentration in soils and alfalfa (Medicago sativa) in field conditions and pot experiments to analyse As soil-forage transference. Results show that most of the available As is transferred.